Altered Blood Molecular Markers of Cardiovascular Function in Rats after Intrauterine Hypoxia and Drug Therapy - Olena Popazova; Igor Belenichev; Oleh Yadlovskyi; Valentyn Oksenych; Aleksandr Kamyshnyi (Current Issues in Molecular Biology, 2023)
Many children and adults who have suffered prenatal hypoxia at an early age develop many serious diseases. This disease is an actual problem of pediatric cardiology and little studied. The aim was to analyze the cardioprotective effect of L-arginine, Thiotriazoline, Angioline, and Mildronate on the cardiovascular system of rats after prenatal hypoxia. Methods: The experiments were carried out on 50 female white rats; intraperitoneal sodium nitrite solution was administered daily to pregnant female rats after 16 days at a dose of 50 mg/kg. Control pregnant rats received saline. The offspring were divided into groups: 1—intact; 2—the control group of rat pups after PH, treated daily with physiological saline; 3—six groups of rat pups after PH, treated daily from the 1st to the 30th day after birth. Heat shock protein HSP70 was determined by enzyme immunoassay, ST2 Nitrotyrosine, and eNOS was observed by ELISA. Results: Angiolin showed a high cardioprotective effect even a month after discontinuation of the drug, and after introduction, the highest decrease in ST2 nitrotyrosine was revealed. Thiotriazoline and L-arginine have an antioxidant effect and a positive effect on eNOS expression, increasing the concentration of HSP70. Mildronate increased the expression of eNOS and the concentration of HSP70 in the blood of experimental rats after a course of administration, but did not show an antioxidant effect and did not reduce the concentration of nitrotyrosine. The results obtained indicate the cardioprotective effect of modulators of the NO system with different mechanisms of action of drugs after prenatal hypoxia.